Left side gallbladder with agenesis of right anterior sector and absence of right hepatic duct. A case report. (2019) - Banchini, Filippo; Ekpo, Ekerette Francis; Conti, Luigi; Capelli, Patrizio
Highlights: Left side gallbladder is more often discovered intraoperatively. A lot of anatomical variations are described. The three-dimensional reconstruction can better highlight intra and extraparenchimal anatomy. The knowledge of this anomaly could be useful both in cholecystectomy technique and liver resection. Abstract: Introduction: Left sided gallbladder is a rare congenital abnormality more often discovered as incidental finding during laparoscopic cholecystectomy requiring surgical challenge to prevent complication. We present a case of a true left sided gallbladder treated with laparoscopic cholecystectomy. Case: A 90 y/o woman with acute abdominal pain was hospitalised and underwent a laparoscopic cholecystectomy. A preoperative CT scan didn't show the variation. Intraoperative finding revealed a true left sided gallbladder that was carefully dissected at the Calot's triangle with identification of the cystic duct and artery. After a complete separation of the gallbladder from the liver, the cystic duct and the artery were safely clipped and transected. CT scan reconstruction reveal agenesis of the right superior sector with simultaneous absence of the right biliary duct. Discussion: True left sided gallbladder is defined as one attached in the left of the ligamentum teres and falciform ligament. This abnormality predispose to a numerous anatomical variation. Unfortunately its finding is more often incidentally during intervention and recognition of such variation could be difficult that can be of high risk for surgical injury. Conclusion: Left sided gallbladder presents a significant challenge to the surgeon and makes it even more difficult to avoid postoperative complications. Therefore, a careful dissection of Calot's triangle and the complete mobilisation of the gallbladder should be done before clipping the cystic duct and artery. However, if a preoperative finding suggests a left sided gallbladder, then an in-depth preoperative anatomical study is advocated.